Neoadjuvant chemotherapy and less invasive surgery for the management of early stage cervical cancer: A brief report from Botswana - Surbhi Grover; Rebecca Luckett; Rohini K. Bhatia; Tlotlo Ralefala; Alexander Seiphetlheng; Doreen Ramogola-Masire; Barati Monare; Lisa Bazzett-Matabele; Kathleen Schmeler; Ponatshego Andrew Gaolebale (Elsevier, 2022)
The majority of deaths from cervical cancer occur in low- and middle- income countries (LMICs). The standard of care for early-stage cervical cancer (FIGO 2018 IA2-IB1) is radical hysterectomy, a procedure performed by trained gynecologic oncologists. However, the lack of gynecologic oncologists in LMICs has required exploration into other methods of treatment for early-stage cervical cancer. A potential course of treatment for early-stage cervical cancer is neoadjuvant chemotherapy followed by simple hysterectomy and pelvic lymph node sampling, which can be performed by a general gynecologist. We gathered data for 8 women who underwent this method of treatment and found that cause-specific survival was 100% over a 3.5-year median follow-up. These findings support the exploration for this method of treatment for early-stage cervical cancer in LMICs, which would improve access to treatment for these women and hopefully reduce the high burden of cervical cancer related deaths in LMICs.